Moderate-Intensity Exercise Improves Mesenteric Arterial Function in Male UC Davis Type-2 Diabetes Mellitus (UCD-T2DM) Rats: A Shift in the Relative Importance of Endothelium-Derived Relaxing Factors (EDRF) - Md Rahatullah Razan; Said Amissi; Rifat Ara Islam; James L. Graham; Kimber L. Stanhope; Peter J. Havel; Roshanak Rahimian (Biomedicines, 2023)
The beneficial cardiovascular effects of exercise are well documented, however the mechanisms by which exercise improves vascular function in diabetes are not fully understood. This study investigates whether there are (1) improvements in blood pressure and endothelium-dependent vasorelaxation (EDV) and (2) alterations in the relative contribution of endothelium-derived relaxing factors (EDRF) in modulating mesenteric arterial reactivity in male UC Davis type-2 diabetes mellitus (UCD-T2DM) rats, following an 8-week moderate-intensity exercise (MIE) intervention. EDV to acetylcholine (ACh) was measured before and after exposure to pharmacological inhibitors. Contractile responses to phenylephrine and myogenic tone were determined. The arterial expressions of endothelial nitric oxide (NO) synthase (eNOS), cyclooxygenase (COX), and calcium-activated potassium channel (KCa) channels were also measured. T2DM significantly impaired EDV, increased contractile responses and myogenic tone. The impairment of EDV was accompanied by elevated NO and COX importance, whereas the contribution of prostanoid- and NO-independent (endothelium-derived hyperpolarization, EDH) relaxation was not apparent compared to controls. MIE 1) enhanced EDV, while it reduced contractile responses, myogenic tone and systolic blood pressure (SBP), and 2) caused a shift away from a reliance on COX toward a greater reliance on EDH in diabetic arteries. We provide the first evidence of the beneficial effects of MIE via the altered importance of EDRF in mesenteric arterial relaxation in male UCD-T2DM rats.